Organic Carbon and Physical Properties in Sandy Soil after Conversion from Degraded Pasture to Eucalyptus in the Brazilian Cerrado - Sena, Karla Nascimento [UNESP]; Maltoni, Katia Luciene [UNESP]; Faria, Glaucia Amorim [UNESP]; Rodrigues Cassiolato, Ana Maria [UNESP] (Soc Brasileira De Ciencia Do Solo, 2017)
Soil is currently seen as the most relevant carbon sink and the most effective carbon stabilizer. In contrast, agriculture is the second largest C emitter, after burning of fossil fuels. This organic carbon (OC) introduced into the soil, mainly via organic matter (OM), is essential for several soil properties and plays an extremely important role in sandy soils. The objective of this study was to describe the changes in the amounts and pools of OC and the influence thereof on some physical soil properties in areas converted from pasture to eucalyptus. The following areas were analyzed: a degraded pasture (PAST), two areas of pasture-eucalyptus conversion after 2 and 15 years (EU02 and EU15, respectively) and a preserved Cerrado area (CER) in the east of the state of Mato Grosso do Sul. Soil samples were taken from the 0.00-0.05, 0.05-0.10, and 0.10-0.30 m layers. The OC was measured and analyzed, the carbon pool (CP) calculated, aggregate stability, bulk density (BD), and macro-and microporosity determined, and total porosity (TP) calculated to analyze the influence of land use on soil properties. The experimental design was completely randomized, and four clusters per area were established, with nine subsampling points, for a total of 36 subsamples per area, organized in 20 x 20 m grids, The soil under natural vegetation (preserved Cerrado) was used as a control. The change from CER to commercial cultivation accelerates the process of OC loss (reductions of 25-35 %) and reductions in soil physical quality. In the PAST area, OC was reduced by 30 % in the 0.00-0.05 m layer. Cumulative OC and CP were highest in the 0.00-0.05 m layer and decreased in the deeper layers in all land use treatments. Organic C in the 0.10-0.30 m layer was not influenced by land use, indicating the possibility of OC persistence in the soil for longer periods. Macroporosity and total porosity may be considered appropriate in CER and EU15, whereas the conditions for plant development in PAST and EU02 were restrictive. Land use systems reduced OC and the CP, indicating anthropogenic disturbance of the soil compared to CER. Fifteen years after planting eucalyptus in the pasture area, signs of recovery of some soil physical properties were observed, e.g., reduced BD and increased TP.
Keywords: aggregate stability; carbon pool; Oxisols; anthropogenic soils